Molecular Dynamics Simulations of Voltage-Gated Cation Channels: Insights on Voltage-Sensor Domain Function and Modulation - Delemotte, Lucie; Klein, Michael L.; TAREK, Mounir (Frontiers in Pharmacology, 2012)
Since their discovery in the 1950s, the structure and function of voltage gated cation channels (VGCC) has been largely understood thanks to results stemming from electrophysiology, pharmacology, spectroscopy and structural biology. Over the past decade, computational methods such as molecular dynamics (MD) simulations have also contributed, providing molecular level information that can be tested against experimental results, thereby allowing the validation of the models and protocols. Importantly, MD can shed light on elements of VGCC function that cannot be easily accessed through “classical” experiments. Here, we review the results of recent MD simulations addressing key questions that pertain to the function and modulation of the VGCC’s voltage sensor domain (VSD) highlighting: 1) the movement of the S4-helix basic residues during channel activation, articulating how the electrical driving force acts upon them; 2) the nature of the VSD intermediate states on transitioning between open and closed states of the VGCC; and 3) the molecular level effects on the VSD arising from mutations of specific S4 positively charged residues involved in certain genetic diseases.